Auswirkungen der COVID-19-Pandemie auf die gynäkologische und geburtshilfliche Leistungserbringung eines universitären Maximalversorgers in Deutschland - Griewing, Sebastian; Wagner, Uwe; Lingenfelder, Michael; Heinis, Sylvia; Schieffer, Bernhard; Markus, Birgit (Geburtshilfe und Frauenheilkunde, 2022)
Introduction The COVID-19 pandemic has been the cause of drastic measures within the national health system. This led us to analyze the clinical and economic performance indicators for gynecology and obstetrics services at the University Hospital of Marburg, which is one of the regional maximum care university hospitals. Therefore, we evaluated the impact of the pandemic on monthly inpatient and outpatient case numbers and the associated ICD and DRG codes, in order to identify any shortcomings in the care provided.Methods and Materials The study is based on a retrospective analysis of data relating to inpatient and outpatient cases that received treatment from 2016 to 2020. We used QlikView, the hospital’s internal performance monitoring program, to evaluate the data from 9487 cases from the gynecology department and 19597 cases from the obstetrics department.Results In line with the nationwide dynamics of the pandemic, we observed a 6% drop in the number of inpatient gynecology cases, while the volume of obstetrics cases rose by 11% in 2020. Overall, the impact on outpatient services was less severe. We also observed a location-specific drop in the number of C50 “malignant neoplasm of breast” cases by 7.4%, and a 14% drop in the number of C56 “malignant neoplasm of ovary” cases. A return to the level of service delivered in the previous year was achieved in three months for outpatient services, and in five months for inpatient services.Conclusion The negative effects of the COVID-19 pandemic primarily affected the gynecology clinic. An increase in obstetrics cases was achieved due to public trust in the safety of the university hospital care, and the service offered of allowing prospective fathers to take part in the birthing process following a rapid test. The return to a pre-pandemic level of service continues to be sluggish, while the outpatient sector, which was less affected in the first place, is showing a more rapid recovery. The location-specific decrease in C50 and C56 diagnoses is concerning, and needs to be assessed from an epidemiological perspective. The impact of the pandemic on case numbers is also reflected in the financial performance indicators.
Keywords: COVID-19; Pandemie; Versorgungsforschung; Maximalversorger; Universitätsklinikum